2015
DOI: 10.1002/anie.201410041
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Two Homo‐chromophoric H‐Aggregates in DNA‐Assembled Alternating Dye Stacks

Abstract: The understanding and description of collectively excited multichromophores is of crucial importance for many areas of basic and applied research. DNA has been used for the construction of well-defined heterochromophoric stacks. Electronic coupling among non-adjacent chromophores of the same type leads to the co-existence of PDI and pyrene H-aggregates in hybrids composed of alternating chromophore stacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…In ethanol, the oligomer is very soluble and the spectrum closely resembles that of the phenanthrene monomer (Supporting Information). [48][49][50][51][52][53] Phenanthrene aggregation leads to the disappearance of the 270 nm band and the occurrence of an H-band (243 nm). [48][49][50][51][52][53] Phenanthrene aggregation leads to the disappearance of the 270 nm band and the occurrence of an H-band (243 nm).…”
mentioning
confidence: 99%
“…In ethanol, the oligomer is very soluble and the spectrum closely resembles that of the phenanthrene monomer (Supporting Information). [48][49][50][51][52][53] Phenanthrene aggregation leads to the disappearance of the 270 nm band and the occurrence of an H-band (243 nm). [48][49][50][51][52][53] Phenanthrene aggregation leads to the disappearance of the 270 nm band and the occurrence of an H-band (243 nm).…”
mentioning
confidence: 99%
“…ds(Sp/PN) showed broadened absorption bands from λ =600 to 800 nm of the pyrrolidine‐substituted PDI . The absorption spectrum of dsDNA containing both PH and PN (PH/PN) was almost consistent with the superposition of the spectra of PH and PN; this means that no strong electronic coupling exists in the ground state between PH and PN . The fluorescence spectra of the PDI/DNA conjugates are shown in Figure b.…”
Section: Resultsmentioning
confidence: 84%
“…In a DNA scaffold, an alternating fashion were arranged by pyrene and perylenediimide (PDI) molecules. The observation of electronic coupling between chromophores of the same type in alternating arrangements indicated that the pyrene H-aggregates and PDI co-exist in p-stacked hetero-aggregates [38]. …”
Section: Small Molecules Modified Dnamentioning
confidence: 99%